Análise do equilíbrio e da qualidade de vida de idosos com Alzheimer e a influência na qualidade de vida do Cuidador - Leite, Mariana Adami [UNESP]; Navega, Marcelo Tavella [UNESP]; Navega, Flávia Roberta Faganello [UNESP] (My University, 2010)
With the growing aging population will be an increase of chronic degenerative diseases such as dementia. Among the various forms of dementia Alzheimer’s disease (AD) is the most prevalent. In individuals with AD, there is a loss in the processing of sensory information, which may aggravate the imbalance and falls. As the disease progresses, the individual lose the ability to function independently, becoming dependent on a caregiver. This study aimed to analyze the balance of the mental state and quality of life of individuals with AD, to determine whether a correlation exists between these variables and analyze the influence on quality of life of caregivers. This study was conducted with thirty individuals (82.86 ± 9.07 years) with AD, both sexes, and their caregivers. The evaluation of the balance was accomplished by the Scale of Functional Balance of Berg (EEFB), the cognitive function for the Mini-exam of the Mental State (MEEM), and the quality of life (QV) for the scale “life Quality - Disease of Alzheimer “ (QdV - DA) that is composed for three versions: patient, caregiver and family The data were analyzed by coefficient of correlation of Spearman. The balance analyses (EEFB=32,17 ± 13,26 points) shows increased in the risk of falls in the elderly and negative correlation (R = - 0,55, p <0,01) with age and good correlation with MEEM (R=0,63 p <0,01). Already in relation of the MEEM and QV, can observed correlation between the familiar version and the MEEM ((R=0,40 p=0,02). In Relation the versions of the QV questionnaire, found significant correlation among: QdV-DA patient X caregiver (R=0,41 p=0,02), QdV-DA patient X family (R=0,40 p=0,03). In this way we can conclude that the individuals with DA, appraised in this study, present a deficit in the balance, so much related with the age as with to the cognitive decline, and the greater the cognitive decline worse the impression of caring about the QOL of their family, and still, that the worsening in the quality of the patient’s life contemplates in a worsening in the quality of your caregiver’s life.

Introdução: Com o crescente envelhecimento populacional haverá um aumento das doenças crônico degenerativas como as síndromes demenciais. Dentre as diversas formas de síndromes demênciais a Doença de Alzheimer (DA), é a mais prevalente. Nos indivíduos com DA, há uma perda no processamento das informações sensoriais, o que pode agravar o desequilíbrio e quedas. Com a progressão da doença, o indivíduo perde a capacidade de funcionar de modo independente, tornando-se dependente de um cuidador. Objetivos: Este estudo teve como objetivo analisar o equilíbrio o estado mental e a qualidade de vida de indivíduos com DA, verificar se existe correlação entre essas variáveis e analisar a influência na qualidade de vida dos cuidadores. Método: Fizeram parte desse estudo 30 sujeitos acometidos com DA de ambos os gêneros, com idade média de 82,86 ± 9,07 anos e seus cuidadores. A avaliação do equilíbrio foi realizada pela Escala de Equilíbrio Funcional de Berg (EEFB), a função cognitiva pelo o MiniExame do Estado Mental (MEEM), e a QV, dos pacientes e cuidadores, pela escala “Qualidade de vida – Doença de Alzheimer” (QdV- DA). Os dados foram analisados pelo coeficiente de correlação de Spearman. O nível de significância utilizado foi de 5% (p≤ 0,05). Resultados: A análise do Equilíbrio (EEFB=32,17±13,26 pontos) mostrou aumento no risco de quedas dos idosos, correlação negativa (R= - 0,55, p<0,01) com a idade e boa correlação com o MEEM (R=0,63,p<0,01). Já em relação ao MEEM e a QV, pode-se observar correlação entre a versão QV-familiar e o MEEM (R=0,40 p=0,02). Em relação às versões do Questionário de QV, foram encontradas correlações Significativas entre: QdV-DA paciente X cuidador (R=0,41p=0,02); QdV-DA paciente X familiar (R=0,40 p=0,03). Conclusão: Dessa forma podemos concluir que os indivíduos com DA, avaliados neste estudo, apresentam um déficit no equilíbrio, tanto relacionado com a idade quanto com ao declínio cognitivo, e quanto maior o declínio cognitivo pior a impressão do cuidador sobre a QV do seu familiar, e ainda, que a piora na qualidade de vida do paciente reflete em uma piora na QV de seu cuidador.
Analysis of the balance and the quality of life of the elderly with Alzheimer and the caregiver quality of life influence
Keywords: qualidade de vida; idoso; cuidador; alzheimer